Terrace Morpho-Sedimentary Sequences on the Sibari Plain (Calabria, Southern Italy): Implication for Sea Level and Tectonic Controls - Federica Lucà; Andrea Brogno; Vincenzo Tripodi; Gaetano Robustelli (Geosciences, 2022)
The Sibari Plain (northeastern Calabria) shows a well-developed stair of late Quaternary marine/coastal terraces resulting from the interaction between sea level fluctuations and tectonic uplift. This paper (i) provides a stratigraphic description of terraced deposits between the Raganello and Coscile rivers, (ii) assesses the relative controls of eustacy and uplift on the staircase formation, and (iii) unravels the Quaternary morphosedimentary evolution of the study area. A geomorphological approach was coupled with stratigraphic field surveys. Photo interpretation, topographic map analyses, and field surveys allowed us to map ten orders of terraces forming telescopically incised valley-fills. Based on the uppermost position of foreshore deposits on inner margins and an average uplift rate of ~1 mm/y, inferred from the Marine Isotope Stage (MIS) 5.5, terraces were correlated with highstands. Sedimentological and stratigraphic analyses allowed us to recognize four assemblages of genetically associated sedimentary facies related to superimposed and juxtaposed coastal and alluvial systems, showing a seaward-stepping architecture. Based on stratal geometry and facies association, we argue that alluvial/fluvial sediments and coastal depositional systems formed contemporaneously along the same terrace. Terrace arrangement resulted from repeated cycles of valley incision (sea level fall) and aggradational to progradational stacking pattern (sea level rise and highstands) in a framework of sustained uplift.